2016
DOI: 10.1371/journal.pone.0166557
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Extract from Lithocarpus polystachyus Rehd. Promote Glycogen Synthesis in T2DM Mice

Abstract: The purpose of this study was to investigate the effects of leaf extract from Lithocarpus polystachyus Rehd. on type II diabetes mellitus (T2DM) and the active ingredients of this effect. In addition, this study determined, for the first time, the underlying molecular and pharmacological mechanisms of the extracts on hyperglycemia using long-term double high diet-fed and streptozotocin (STZ) induced type II diabetic mice. In the present study, leaf extract, phloridzin and trilobatin were assessed in vivo (gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…Trilobatin (TLB; Figure 1A ), a small molecule monomer, is considered as a novel bioactive compound of Lithocarpus polystachyus Rehd. Previous studies have demonstrated that TLB exhibited anti-oxidant and anti-inflammatory activities (Fan et al, 2015 ; Wang J. et al, 2016 ), but until now, the protective effect of TLB on oxidative stress-induced cellular mitochondrial dysfunction and apoptosis in neuron still remains a mystery. Under this scenario, the aim of this study was designed to assess whether TLB exerts salutary effects on H 2 O 2 -induced PC12 cell injury and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Trilobatin (TLB; Figure 1A ), a small molecule monomer, is considered as a novel bioactive compound of Lithocarpus polystachyus Rehd. Previous studies have demonstrated that TLB exhibited anti-oxidant and anti-inflammatory activities (Fan et al, 2015 ; Wang J. et al, 2016 ), but until now, the protective effect of TLB on oxidative stress-induced cellular mitochondrial dysfunction and apoptosis in neuron still remains a mystery. Under this scenario, the aim of this study was designed to assess whether TLB exerts salutary effects on H 2 O 2 -induced PC12 cell injury and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the proof of principle demonstrations herein, our previous work has shown that anthocyanin can be used to synthesize nanoparticles or for functional foods, and Castañeda‐Ovando et al discuss a variety of other applications such as cosmetic and pharmaceutical uses. We have shown the simple extraction and cryoconcentration of anthocyanin from B. oleracea using block cryoconcentration with partial gravitational thawing as an effective method for creating value added products.…”
Section: Resultsmentioning
confidence: 77%
“…4,5 Plants that are rich in anthocyanins include blueberries, raspberries, concord grapes, and red cabbage. 6 Anthocyanin extracts are used as food additives, 7,8 medicinal supplements, 9,10 molecular templates for nanomaterial synthesis, 11,12 various cosmetic applications, 13 dyesensitized solar cells, 14,15 and as biodetectors. 16,17 Due to the diverse applications of anthocyanins, research on the development of this value added agricultural product has increased in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that trilobatin has anti-oxidative 9,10 , anti-viral and anti-in ammatory activities 11,12 . Trilobatin also exhibits anti-hyperglycemic properties by accelerating liver glycogen synthesis, decreasing oxidative stress, increasing the expression of glucokinase, and up-regulating the expression of insulin receptor substrate (IRS) on long-term double high fat-diet and streptozotocin (STZ) induced type 2diabetic mice 13 . Similar to other dihydrochalcones, phlorizin (a dual SGLT1/SGLT2 inhibitor) 14 , phloretin (a GLUT2 inhibitor) 15 , and acarbose (an alpha-glucosidase inhibitor) 16,17 , our previous works demonstrated that trilobatin could be bind with SGLT1/2 18 .…”
Section: Introductionmentioning
confidence: 99%